Iron, Ferritin, Hereditary Ferritinopathy, and Neurodegeneration - Muhoberac, Barry B.; Vidal, Ruben (Frontiers in Neuroscience, 2019)
Cellular growth, function and protection require proper iron management, and ferritin plays a physiologically crucial role as the major iron sequestration and storage protein. Ferritin is a 24 subunit spherical shell protein composed of both light (FTL) and heavy chain (FTH1) subunits, possessing complimentary iron-handling functions and forming pores of 3-fold and 4-fold symmetry. Iron uptake through the 3-fold pores is well-defined, but the unloading process somewhat less and generally focuses on lysosomal ferritin degradation although it may have an additional, energetically efficient pore mechanism. Hereditary Ferritinopathy (HF) or neuroferritinopathy is an autosomal dominant neurodegenerative disease caused by mutations in the FTL C-terminal sequence, which in turn cause disorder and unraveling at the 4-fold pores allowing iron leakage and enhanced formation of toxic, improperly coordinated iron (ICI). Histopathologically, HF is characterized by iron deposition and formation of ferritin inclusion bodies (IBs) as the cells overexpress ferritin in an attempt to address iron accumulation while lacking the ability to clear ferritin and its aggregates. Overexpression and IB formation tax cells materially and energetically, i.e., their synthesis and disposal systems, and may hinder cellular transport and other spatially dependent functions. ICI causes cellular damage to proteins and lipids through reactive oxygen species (ROS) formation because of high levels of brain oxygen, reductants and general metabolism, taxing cellular repair. Iron can cause protein aggregation both indirectly by ROS-induced protein modification and destabilization, and more directly as with mutant ferritin through C-terminal bridging. Iron release and ferritin degradation are also linked to cellular misfunction through ferritinophagy, which can release sufficient iron to initiate the unique programmed cell death process of ferroptosis causing ROS formation and lipid peroxidation. But IB buildup suggests suppressed ferritinophagy, with elevated iron from 4-fold pore leakage together with aggregation leading to a long-term ferroptotic-like state in HF. Several of these processes have parallels in cell line and mouse models. This review addresses the roles of ferritin structure and function within the above-mentioned framework, as they relate to HF and associated disorders characterized by abnormal iron accumulation, protein aggregation, oxidative damage, and the resulting contributions to cumulative cellular stress and death.